Communication Rationality in Community Empowerment Activities through CSR Program of PT Pertamina Patra Niaga Fuel Terminal Rewulu: PETRA (Pengolahan Tempe Tradisional) Program & Jati Husada Mulya Producer Cooperative - Erwin Rasyid; Mashithohiyah, Nur (Prospect Publishing, 2025)
Poverty and unequal access to resources are still problems in Indonesia, so community empowerment through CSR is a strategic step. This research aims to analyze the communication rationality in community empowerment activities through PT Pertamina Rewulu's CSR programs, namely the PETRA Program and the Jati Husada Mulya Mandiri Producer Cooperative. This research uses a qualitative method with a phenomenological approach, through in-depth interviews, participatory observation, and document analysis. The results showed that the communication was open, participatory, and egalitarian according to Jurgen Habermas' communicative rationality theory, where the community was not only the executor, but also involved in planning, decision-making, and program evaluation. The dialog process that is built allows the achievement of validity claims including truth claims, accuracy claims, and honesty claims. The research findings showed an increase in skills, relationships, and economic productivity of group members, as well as the formation of a sense of community ownership of the program. This research reinforces that CSR implementation based on rational communication not only fulfills corporate obligations, but also increases community empowerment and independence in a sustainable manner.